Analisis Pengalaman Interaksi Pengguna Terhadap Permainan Catur Sebagai Obyek Augmented Reality Menggunakan Game Experience Questionaire - Ryan Edbert Jeremiah; Wibisono Sukmo Wardhono; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The interaction between human and computer is an integral part in the present life along with the development of information technology. Similarly in the development of information technology that supports the interaction with users as well as augmented reality, especially in this research is a game of chess with game board application. This study aims to integrate the game of chess as an object of augmented reality by considering interactive elements to improve the user experience and analyze the user experience of chess game applications displayed as augmented reality objects using Game Experience Questionare (GEQ) technique. The research method used is the development and evaluation, which includes evaluation planning, evaluation and evaluation results evaluation. The data were collected using questionnaires with Likert scale with range of five (1,2,3,4,5). In the Game Experience Questionare (GEQ game used with chess game application with augmented reality technology based on GEQ Core Module, and GEQ Post-Game Module which before being used has been done by expert validation.The results show that game of chess by conveying the elements interactive successfully integrated as a static augmented reality object with a background on the chess game showing real environment captured via webcam.